Neodymium-iron-boron magnet without heavy rare earth addition and method for producing the same
Patent Information
- Application Number
- CN202511291548.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-10
AI Technical Summary
这些杂质易与稀土元素结合形成高熔点氧化物、氮化物或碳化物,钉扎晶界,阻碍液相烧结过程中的晶界迁移,导致磁体密度不均、晶粒异常长大,进而降低矫顽力与方形度
[0061] The neodymium iron boron magnet of this invention, under the condition of no heavy rare earth addition, achieves Hcj of 17kOe-23kOe, Br of 12kGs-15kGs, and squareness of not less than 94% through the synergistic control of composition, grain boundaries, and three-stage tempering treatment. This provides a high-performance, low-cost heavy rare earth-free solution for wind power generation, new energy vehicles, industrial servo systems, and humanoid robots.
Smart Images

Figure CN121191875B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of permanent magnet technology, and in particular to a neodymium iron boron magnet without heavy rare earth elements and its preparation method. Background Technology
[0002] Sintered NdFeB magnets are widely used in high-end fields such as wind power generation, new energy vehicle drive motors, industrial servo motors, and humanoid robot joints due to their excellent magnetic properties. However, there is an inherent contradiction between the remanence (Br) and intrinsic coercivity (Hcj) of NdFeB magnets. Traditional techniques involve introducing heavy rare earth elements such as Tb and Dy to partially replace the main phase (R2T). 14 Nd in B) to enhance the magnetocrystalline anisotropy field (H a This increases coercivity. However, Tb and Dy are scarce and expensive, and they exhibit antiferromagnetic coupling with Fe, which, while increasing coercivity, reduces saturation magnetization (Ms), leading to a decrease in remanence. Furthermore, heavy rare earth elements readily form (Nd,HRE)₂Fe at grain boundaries. 14 While the B-shell can suppress demagnetization nuclei, it also weakens remanence. Therefore, developing "heavy rare earth" or "low heavy rare earth" NdFeB magnets has become a strategic direction for the sustainable development of the permanent magnet industry.
[0003] Without adding heavy rare earth elements, the improvement of coercivity mainly depends on the optimization of microstructure. According to the phenomenological formula for coercivity, Hcj = α·H a -N eff ·Ms, where α and N eff These are microstructural parameters, reflecting the demagnetizing coupling efficiency and demagnetizing factor of grain boundaries to the host phase, respectively. In systems without heavy rare earth elements, H... a Since Ms can be considered a constant, the key to improving Hcj lies in reducing N. eff Furthermore, α can be increased by refining the grains, optimizing the distribution of grain boundary phases, and suppressing exchange coupling between grains. However, existing technologies still have significant shortcomings.
[0004] The methods for controlling grain boundaries are limited and have a narrow process window. Existing technologies propose low-temperature hydrogen breaking (HD) combined with low-temperature tempering to control the grain boundary phase, but low-temperature treatment easily leads to uneven distribution of the grain boundary phase, poor consistency in batch production, and low magnet squareness (Hk / Hcj), making it difficult to meet the rectangularity requirements of the demagnetization curve at high operating temperatures (≥120℃).
[0005] The auxiliary alloying process is complex and costly. Existing technologies improve grain boundaries by adding Pr-containing auxiliary alloys or using heavy rare earth-free auxiliary alloy grain boundary diffusion technology. However, the design of auxiliary alloy composition is complicated and requires the additional preparation of alloy powder. Furthermore, the grain boundary diffusion process requires coating with organic binders, which can easily introduce impurities such as carbon and oxygen, deteriorating the surface quality and corrosion resistance of the magnet.
[0006] Controlling the iron content at grain boundaries is difficult. In traditional sintering processes, Fe-rich phases tend to accumulate at triangular grain boundaries, forming antimagnetic nuclei and reducing coercivity. Current technologies lack effective means for quantitative control of the iron content in grain boundary phases, resulting in limited improvement in the coercivity of heavy rare earth magnets, typically not exceeding 15 kOe.
[0007] Controlling non-metallic impurities (C, N, O) is also a challenge in the industry. These impurities easily combine with rare earth elements to form high-melting-point oxides, nitrides, or carbides, pinning grain boundaries and hindering grain boundary migration during liquid-phase sintering. This leads to uneven magnet density, abnormal grain growth, and consequently reduced coercivity and squareness. Existing technologies for controlling impurity content mostly focus on the final magnet, neglecting closed-loop management of the entire process from melting and powdering to sintering, resulting in large batch-to-batch performance fluctuations.
[0008] In summary, the development of heavy rare earth NdFeB magnets still faces the ternary balance challenge of "high coercivity-high squareness-low cost," and urgently requires a systematic solution from composition design, process route to impurity control to achieve precise control of grain boundary structure and break through existing technological bottlenecks. Summary of the Invention
[0009] The purpose of this invention is to address the shortcomings of existing technologies by providing a neodymium iron boron magnet without heavy rare earth elements and its preparation method.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] The first aspect of the present invention is to provide a neodymium iron boron magnet without heavy rare earth elements, wherein the general formula of the neodymium iron boron magnet is:
[0012] R x T 100-x-y-z-a-b Tm y Tg z B a H b (Formula I)
[0013] R represents at least two of the elements Nd, Pr, or Ce;
[0014] T represents at least one of the elements Fe or Co, and the T includes at least the element Fe;
[0015] Tm represents at least one of the elements Al, Si, Cu, Ga, or Sn, and Tm includes at least one of the elements Cu or Ga.
[0016] Tg represents at least one of the elements Ti, Zr, Nb, or Mo;
[0017] B represents element B;
[0018] H indicates unavoidable heavy rare earth impurity elements;
[0019] x represents the atomic percentage of R in the neodymium iron boron magnet, where x ∈ [13, 3, 17);
[0020] y represents the atomic percentage of Tm in the neodymium iron boron magnet, where y ∈ [0.3, 5);
[0021] z represents the atomic percentage of Tg in the neodymium iron boron magnet, where z ∈ [0.1, 0.5).
[0022] a represents the atomic percentage of B in the neodymium iron boron magnet, where a ∈ [5, 5.8).
[0023] b represents the atomic percentage of H in the neodymium iron boron magnet, where b ∈ [0, 0.2).
[0024] 100-xyzab represents the atomic percentage of T in the neodymium iron boron magnet;
[0025] Furthermore, the neodymium iron boron magnet satisfies:
[0026]
[0027] Wherein, [T] represents the 100-xyzab, [B] represents a, [Cu] represents the atomic percentage of Cu element in the NdFeB magnet, and [Ga] represents the atomic percentage of Ga element in the NdFeB magnet;
[0028] Furthermore, the neodymium iron boron magnet has a main phase R2T. 14 B, and grain boundary phases.
[0029] The atomic percentage (x) of R (rare earth element) is limited to 13at%-17at, which can maintain remanence of 1.2T-1.5T under heavy rare earth conditions; if it is too low, the grain boundary phase is insufficient and the coercivity decreases, and if it is too high, the remanence and corrosion resistance deteriorate.
[0030] The atomic percentage (y) of Tm (transition metal element) is controlled between 0.3at% and 5at. It can form a low-melting-point grain boundary phase with rare earth elements. Excessive Tm will deteriorate remanence and squareness.
[0031] The atomic percentage (z) of Tg (high melting point element) is 0.1at%-0.5at%. Borides precipitate at triangular grain boundaries to refine the grains. Excessive Tg can easily lead to non-dense sintering or abnormal grain growth.
[0032] The atomic percentage (a) of boron (B) is set to 5 at%-5.8 at% to ensure the main phase R2T 14 B generates sufficient amounts and inhibits the B-rich phase; however, excessive amounts reduce coercivity.
[0033] The atomic percentage (b) of H (an unavoidable heavy rare earth impurity element) is less than 0.2 at%, which is a trace amount of heavy rare earth introduced from raw materials and equipment. It must be strictly controlled to avoid batch fluctuations.
[0034] The composition must simultaneously satisfy formulas (II) and (III) to make the atomic percentage of boron element close to a positive ratio of 2:14:1 and reduce residual Fe at the grain boundary, thus inhibiting the generation of antimagnetic nuclei; Cu / Ga elements, together with rare earth elements and Fe elements, form a low-melting-point R-Fe-(Cu,Ga) phase, which thickens the grain boundary and enhances demagnetization coupling.
[0035] Preferably, the magnet density of the neodymium iron boron magnet is 7.44 g / cm³. 3 -7.55g / cm 3 .
[0036] The magnet density is controlled at 7.44 g / cm³. 3 -7.55g / cm 3 Excessive concentration leads to grain coarsening and decreased coercivity, while insufficient concentration results in inadequate remanence and corrosion resistance.
[0037] Preferably, the main phase R2T 14 The average grain size of B is 3μm-8μm.
[0038] Principal phase R2T 14 The average grain size of B is 3μm-8μm. Grain refinement reduces the effective demagnetization factor and further improves coercivity.
[0039] Preferably, the atomic percentage of Fe element in the grain boundary phase is 1%-20%.
[0040] A second aspect of the present invention is to provide a method for preparing a neodymium iron boron magnet as described above, comprising the steps of:
[0041] S1. Vacuum melting of raw materials according to the elemental atomic percentage of the neodymium iron boron magnet to obtain a casting sheet;
[0042] S2. The casting sheet is subjected to hydrogen crushing and air jet milling in sequence to obtain fine powder;
[0043] S3. The fine powder is subjected to orientation forming, vacuum sintering, and multi-stage tempering in sequence to obtain the neodymium iron boron magnet.
[0044] Preferably, the steps further include:
[0045] S10. Vacuum melt the raw material according to the element atomic percentage of the neodymium iron boron magnet to obtain a casting sheet;
[0046] S11. Detect the mass percentage content of non-metallic impurity elements in the casting: If the mass percentage content of non-metallic impurity elements in the casting is 200ppm-700ppm, proceed to the next step.
[0047] S2. The casting sheet is subjected to hydrogen crushing and air jet milling in sequence to obtain fine powder;
[0048] S30. The fine powder is subjected to orientation forming, vacuum sintering, and multi-stage tempering in sequence to obtain a magnet.
[0049] S31. Detect the mass percentage content of non-metallic impurity elements in the magnet: If the mass percentage content of non-metallic impurity elements in the magnet is 800ppm-1600ppm, and the difference between the mass percentage content of non-metallic impurity elements in the magnet and the mass percentage content of non-metallic impurity elements in the casting is less than 1000ppm, then the obtained magnet is the neodymium iron boron magnet.
[0050] Impurities are controlled in a closed loop throughout the entire process: the mass percentage of non-metallic impurity elements (such as C, N, O, etc.) in the casting is 200ppm-700ppm, and the mass percentage of non-metallic impurity elements in the magnet after multi-stage tempering is no higher than 1600ppm, and the increment is less than 1000ppm, so as to ensure the squareness and batch consistency.
[0051] Preferably, the temperature of the vacuum sintering treatment is 1030℃-1080℃.
[0052] Preferably, the multi-stage tempering process includes:
[0053] M1, first-stage tempering, followed by cooling;
[0054] The temperature of the first-stage tempering treatment is 800℃-950℃, and the duration of the first-stage tempering treatment is 2h-6h.
[0055] M2, two-stage tempering treatment, followed by cooling treatment;
[0056] The temperature of the secondary tempering treatment is 600℃-800℃, and the duration of the secondary tempering treatment is 2h-6h.
[0057] M3, three-stage tempering treatment, followed by cooling treatment;
[0058] The temperature of the three-stage tempering treatment is 450℃-650℃, and the duration of the three-stage tempering treatment is 2h-6h.
[0059] By employing a first-stage tempering treatment at 800℃-950℃, a second-stage tempering treatment at 600℃-800℃, and a third-stage tempering treatment at 450℃-650℃, the grain boundary phase is fully transformed, the lattice mismatch is reduced, and Hcj can be further increased by 2kOe-10kOe.
[0060] The present invention adopts the above technical solution and has the following technical effects compared with the prior art:
[0061] The neodymium iron boron magnet of this invention, under the condition of no heavy rare earth addition, achieves Hcj of 17kOe-23kOe, Br of 12kGs-15kGs, and squareness of not less than 94% through the synergistic control of composition, grain boundaries, and three-stage tempering treatment. This provides a high-performance, low-cost heavy rare earth-free solution for wind power generation, new energy vehicles, industrial servo systems, and humanoid robots. Attached Figure Description
[0062] Figure 1 The image shows the microstructure of the neodymium iron boron magnet in Example 3. Detailed Implementation
[0063] The specific embodiments of the present invention will be described in detail below.
[0064] Unless otherwise defined, the technical or scientific terms used in the claims and description shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0065] The word "comprising" or similar terms used in the specification and claims of this patent application mean that the objects preceding "comprising" include the objects listed after "comprising" or their equivalents, and do not exclude other objects.
[0066] The numerical values mentioned in this invention include all values increasing one unit at a time from low to high, assuming that there is at least a two-unit interval between any lower and higher value. For example, if it is said that a component quantity or a physical quantity is better from 1 to 100, 10 to 90, and 20 to 80, it means that values such as 5 to 95, 14 to 76, 23 to 67, 32 to 58, and 41 to 49 are clearly listed in this specification; for values less than 1, 0.0001, 0.001, 0.01, or 0.1 are considered to be a suitable unit. The foregoing examples are for illustrative purposes only; in practice, all combinations of values between the lowest and highest listed values are considered to be clearly listed in this specification in a similar manner.
[0067] In embodiments of the present invention, the preparation steps of the neodymium iron boron magnet without heavy rare earth elements include:
[0068] S10. Place the raw materials, each with a purity of not less than 99.9%, into the crucible of the vacuum induction furnace in descending order of melting point; after sealing the furnace, evacuate to 10°C. -3 Pa-10 -4 Pa, while ensuring the dew point is below -50℃; then argon gas is introduced to 30kPa-50kPa, and smelting is carried out at 1460℃-1530℃. After the material is completely melted, it is held at the temperature for 3min-5min; the temperature of the alloy liquid is reduced to 1420℃-1460℃ and held at the temperature, and then it is continuously poured through the tundish onto the surface of a water-cooled copper roller with a rotation speed of 30r / min-75r / min for rapid solidification. The resulting castings then fall into the water-cooling pan for further cooling.
[0069] S11. Detect the mass percentage content of non-metallic impurity elements in the obtained casting: If the mass percentage content of non-metallic impurity elements in the casting is 200ppm-700ppm, proceed to the next step.
[0070] S2. Place the casting in the reactor, evacuate the reactor, and then introduce hydrogen gas to a positive pressure (positive pressure is the difference between absolute pressure and atmospheric pressure) of 0.1 MPa. When the casting absorbs hydrogen and the positive pressure in the reactor drops to 0.05 MPa-0.06 MPa, re-introduce hydrogen to 0.1 MPa. Repeat the operation until the pressure change does not exceed 0.5% within 10 minutes, at which point hydrogen absorption saturation is determined. Then, while evacuating the reactor, raise the temperature to 400℃-600℃ and hold for 2-6 hours to completely remove hydrogen. Finally, cool the reactor to obtain hydrogen-crushed coarse powder.
[0071] The coarse powder from hydrogen crushing is placed in an air jet mill and placed in an inert atmosphere such as hydrogen, helium, or nitrogen. The nozzle pressure is adjusted to 0.6MPa-0.8MPa, and the high-speed airflow drives the particles to collide with each other to produce fine powder.
[0072] The resulting fine powder can also be mixed with commercially available magnetic powder protective lubricant and / or antioxidant as needed. The amount of magnetic powder protective lubricant is 0.01%-0.1% of the mass of the fine powder, and the amount of antioxidant is 0.01%-0.14% of the mass of the fine powder.
[0073] S3. Orientation molding was completed under an orientation magnetic field of 1.8T-2.5T and a molding pressure of 30MPa-45MPa, resulting in a compact with a density of 3.6g / cm³. -3 -4.0g cm -3 ;
[0074] Optionally, the compact is subjected to cold isostatic pressing at 150MPa-180MPa to increase its density to 4.5g / cm³. -3 –4.6gcm -3 To eliminate internal cracks;
[0075] The compact was placed in a vacuum sintering furnace at 5°C / min. -1 -8℃·min -1 The temperature is increased to 1030℃-1080℃ and held for 3h-8h, and then cooled to obtain the first magnet.
[0076] M1. The first magnet obtained is first tempered at 800℃-950℃ for 2h-6h, and then furnace-cooled or air-cooled to below 100℃ after the holding period.
[0077] M2, then heat to 600℃-800℃ and hold for 2h-6h for secondary tempering treatment, after which furnace cooling or air cooling to below 100℃;
[0078] M3, then heat to 450℃-650℃ and hold for 2-6 hours for secondary tempering treatment. After holding, maintain a temperature of not less than 30℃·min. -1 The second magnet is obtained by cooling it to below 80°C using an air-cooling rate.
[0079] S31. Detect the mass percentage content of non-metallic impurity elements in the obtained second magnet: If the mass percentage content of non-metallic impurity elements in the second magnet is 800ppm-1600ppm, and the difference between the mass percentage content of non-metallic impurity elements in the second magnet and the mass percentage content of non-metallic impurity elements in the casting is less than 1000ppm, then the second magnet is a neodymium iron boron magnet.
[0080] After the magnet was broken, samples were taken from its central area, and the composition was determined using inductively coupled plasma atomic emission spectrometry (ICP). The microstructure was observed using scanning electron microscopy (SEM), and the micro-area composition was confirmed using electron probe microanalysis (EPMA). The magnet was further processed using wire cutting, double-sided grinding, and end-face grinding. The magnetic properties of the cylindrical samples were measured using the NIM standard magnetic measurement system.
[0081] Examples 1-7 and Comparative Examples 1-6
[0082] The NdFeB magnets of Examples 1-7 and Comparative Examples 1-6, along with their elemental atomic percentages and performance parameters, are shown in the table below:
[0083]
[0084]
[0085]
[0086] (Continued)
[0087]
[0088]
[0089]
[0090] (Continued)
[0091]
[0092]
[0093] (Continued)
[0094]
[0095]
[0096] As can be seen from the table above, compared with Example 1, Comparative Example 1 increased the content of element B to a range that does not satisfy Formula (III) of the present invention, resulting in the enrichment of element Fe at the grain boundaries of the final NdFeB magnet, forming a grain boundary structure dominated by iron-rich phase, which led to a significant reduction in the coercivity of the NdFeB magnet, which decreased by about 5 kOe compared with Example 1.
[0097] Compared with Example 2, Comparative Example 2 only slightly increased the content of element B. However, under the synergistic effect of high content of low melting point metal elements and without performing secondary tempering treatment, Fe elements were enriched at the grain boundaries, the distribution of grain boundary phases was discontinuous, and the coercivity of the NdFeB magnet was reduced accordingly.
[0098] Compared with Example 3, Comparative Example 3 did not introduce Al, Cu and Ga elements at all, resulting in a significant deficiency of low-melting-point metal elements at the grain boundaries and a discontinuous distribution of grain boundary phases; even with the subsequent addition of heavy rare earth elements, the coercivity of the NdFeB magnet was still significantly lower than that of Example 3.
[0099] Compared with Example 4, the average grain size of Comparative Example 4 is significantly increased, the proportion of multi-domain grains is increased, and it is easier to form antimagnetic nuclei, which in turn leads to a decrease in coercivity.
[0100] Compared with Example 5, Comparative Example 5 introduced more non-metallic impurity elements during the preparation process, and the content of non-metallic impurity elements was relatively high, forming high-melting-point non-metallic inclusions mainly composed of rare earth carbides, oxides and nitrides. The above-mentioned inclusions reduced the fluidity of the grain boundary phase, making the grain boundary distribution discontinuous, and ultimately leading to a decrease in coercivity.
[0101] Comparative Example 6 simultaneously increased the content of Cu and Ga elements to an excess level, and the second-stage aging temperature deviated from the melting point of the grain boundary phase, resulting in a large amount of Cu element precipitating at the triangular grain boundaries, which led to a significant increase in lattice mismatch and a deterioration in the squareness of the NdFeB magnet.
[0102] The above description is merely a preferred embodiment of the present invention and does not limit the implementation and protection scope of the present invention. Those skilled in the art should realize that any equivalent substitutions and obvious changes made based on the description and illustrations of the present invention should be included within the protection scope of the present invention.
Claims
1. A neodymium iron boron magnet without heavy rare earth elements, characterized in that, The general formula for the neodymium iron boron magnet is: R x T 100-x-y-z-a-b Tm y Tg z B a H b ;in, R represents at least two of the elements Nd, Pr, or Ce; T represents at least one of the elements Fe or Co, and the T includes at least the element Fe; Tm represents at least one of the elements Al, Si, Cu, Ga, or Sn, and Tm includes at least one of the elements Cu or Ga. Tg represents at least one of the elements Ti, Zr, Nb, or Mo; B represents element B; H indicates unavoidable heavy rare earth impurity elements; x represents the atomic percentage of R in the neodymium iron boron magnet, where x ∈ [13, 3, 17); y represents the atomic percentage of Tm in the neodymium iron boron magnet, where y ∈ [0.3, 5); z represents the atomic percentage of Tg in the neodymium iron boron magnet, where z ∈ [0.1, 0.5). a represents the atomic percentage of B in the neodymium iron boron magnet, where a ∈ [5, 5.8). b represents the atomic percentage of H in the neodymium iron boron magnet, where b ∈ [0, 0.2). 100-xyzab represents the atomic percentage of T in the neodymium iron boron magnet; Furthermore, the neodymium iron boron magnet satisfies: Wherein, [T] represents the 100-xyzab, [B] represents a, [Cu] represents the atomic percentage of Cu element in the NdFeB magnet, and [Ga] represents the atomic percentage of Ga element in the NdFeB magnet; Furthermore, the neodymium iron boron magnet has a main phase R2T. 14 B, and grain boundary phases.
2. The neodymium iron boron magnet according to claim 1, characterized in that, The magnet density of the neodymium iron boron magnet is 7.44 g / cm³. 3 -7.55g / cm 3 .
3. The neodymium iron boron magnet according to claim 1, characterized in that, The main phase R2T 14 The average grain size of B is 3μm-8μm.
4. The neodymium iron boron magnet according to claim 1, characterized in that, The atomic percentage of Fe element in the grain boundary phase is 1%-20%.
5. A method for preparing a neodymium iron boron magnet as described in any one of claims 1-4, characterized in that the step... include: S1. Vacuum melting of raw materials according to the elemental atomic percentage of the neodymium iron boron magnet to obtain a casting sheet; S2. The casting sheet is subjected to hydrogen crushing and air jet milling in sequence to obtain fine powder; S3. The fine powder is subjected to orientation forming, vacuum sintering, and multi-stage tempering in sequence to obtain the neodymium iron boron magnet.
6. The preparation method according to claim 5, characterized in that, The steps also include: S10. Vacuum melt the raw material according to the element atomic percentage of the neodymium iron boron magnet to obtain a casting sheet; S11. Detect the mass percentage content of non-metallic impurity elements in the casting: If the mass percentage content of non-metallic impurity elements in the casting is 200ppm-700ppm, proceed to the next step. S2. The casting sheet is subjected to hydrogen crushing and air jet milling in sequence to obtain fine powder; S30. The fine powder is subjected to orientation forming, vacuum sintering, and multi-stage tempering in sequence to obtain a magnet. S31. Detect the mass percentage content of non-metallic impurity elements in the magnet: If the mass percentage content of non-metallic impurity elements in the magnet is 800ppm-1600ppm, and the difference between the mass percentage content of non-metallic impurity elements in the magnet and the mass percentage content of non-metallic impurity elements in the casting is less than 1000ppm, then the obtained magnet is the neodymium iron boron magnet.
7. The preparation method according to claim 5, characterized in that, The vacuum sintering temperature is 1030℃-1080℃.
8. The preparation method according to claim 5, characterized in that, The multi-stage tempering process includes: M1, first-stage tempering, followed by cooling; The temperature of the first-stage tempering treatment is 800℃-950℃, and the duration of the first-stage tempering treatment is 2h-6h. M2, two-stage tempering treatment, followed by cooling treatment; The temperature of the secondary tempering treatment is 600℃-800℃, and the duration of the secondary tempering treatment is 2h-6h. M3, three-stage tempering treatment, followed by cooling treatment; The temperature of the three-stage tempering treatment is 450℃-650℃, and the duration of the three-stage tempering treatment is 2h-6h.
Citation Information
Patent Citations
Non-heavy-rare-earth sintering neodymium iron boron magnet and preparation method thereof
CN108806912A
Neodymium iron boron sintering magnet without heavy rare earth and preparation method thereof
CN108878090A